Makhsomim - Shamir, Yoav (Israel : Breuer, Amit ; Kowarsky, Edna ; Kowarsky, Elionor, 2003)
The West Bank and Gaza Strip have been under Israeli military authority since 1967. Over three million Palestinians live in a nation under Israeli occupation. When they want to move from one village or city to another, to visit relatives or doctors, or to go to work, they have to pass through Israeli checkpoints. After years of terrorist attacks, dozens of these heavily guarded checkpoints have been set up. From 2001 to 2003, director Yoav Shamir has filmed and created an incredibly honest and moving verité record of various occurrences at these checkpoints. This experiential film conveys a saddening series of encounters between the humiliated Palestinians and the heavily armed, often very young soldiers, who sometimes feel uneasy in their commanding roles. But these men are often self-assured, too, apparently taking pleasure in intimidating the Palestinians, having them wait for hours in the burning sun or pouring rain. The tension is palpable when a large group of Palestinian people ignores the order to return and collectively pass the roadblocks. The general impression is one of an endless situation, in which people on both sides are forced into positions that leave little room for human dignity.
Duration: 01:20:00
Keywords: Documentary films